GAMBARAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) MESIN FILLING REAGEN CHOLESTEROL FS DI PT. X - Sharon, Viona Angelica; Sulanjari, Prasti; Azzahra, Fauzia; Sari, Marta Hayu Raras Sita Rukmika (Politeknik META Industri Cikarang, 2025)
One of the manufacturers of in vitro medical diagnostic equipment, PT.X, faces challenges with the production efficiency of a chemical clinic reagent called cholesterol FS. High demand led to continuous machine operation, which resulted in machine problems, particularly during the bottle closure process, which reduced production effectiveness. This experiment aim to analyze the production effectivity using Overall Equipment Effectiveness (OEE) method. Three parameters are used in OEE measurement: Availability, Performance, and Quality. The data acquired through direct observation during the filling of a batch of cholesterol FS reagent, including production volume, downtime, rejected product, etc. The investigation resulted the values of Availability is 85.50%, Performance is 59.66% and Quality is 99.81%. According to the finding, the OEE of filling machine from Cholesterol FS reagent is 48.85%. Therefore, more optimization is required to reduce downtime and boost machine performance in order to raise availability and performance in accordance with the World-Class OEE standard